2016
DOI: 10.1371/journal.pntd.0004371
|View full text |Cite
|
Sign up to set email alerts
|

Markov Model Predicts Changes in STH Prevalence during Control Activities Even with a Reduced Amount of Baseline Information

Abstract: BackgroundEstimating the reduction in levels of infection during implementation of soil-transmitted helminth (STH) control programmes is important to measure their performance and to plan interventions. Markov modelling techniques have been used with some success to predict changes in STH prevalence following treatment in Viet Nam. The model is stationary and to date, the prediction has been obtained by calculating the transition probabilities between the different classes of intensity following the first year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A Markov statistical model was developed to capture soil-transmitted helminth (STH) infection dynamics through rounds of MDA (with benzimidazoles), by Montresor and colleagues in 2013 [ 16 , 17 ]. The authors demonstrated that their model successfully predicted changes in the prevalence of Ascaris lumbricoides , Trichuris trichiura and hookworm (consisting of the two species that infect humans: Ancylostoma duodenale and Necator americanus ) through five rounds of MDA using data collected at baseline and after one round of treatment in Vietnam to parameterize the Markov Transition Probability (MTP) matrix; the essential ingredient of such Markov models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Markov statistical model was developed to capture soil-transmitted helminth (STH) infection dynamics through rounds of MDA (with benzimidazoles), by Montresor and colleagues in 2013 [ 16 , 17 ]. The authors demonstrated that their model successfully predicted changes in the prevalence of Ascaris lumbricoides , Trichuris trichiura and hookworm (consisting of the two species that infect humans: Ancylostoma duodenale and Necator americanus ) through five rounds of MDA using data collected at baseline and after one round of treatment in Vietnam to parameterize the Markov Transition Probability (MTP) matrix; the essential ingredient of such Markov models.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated that their model successfully predicted changes in the prevalence of Ascaris lumbricoides , Trichuris trichiura and hookworm (consisting of the two species that infect humans: Ancylostoma duodenale and Necator americanus ) through five rounds of MDA using data collected at baseline and after one round of treatment in Vietnam to parameterize the Markov Transition Probability (MTP) matrix; the essential ingredient of such Markov models. The predictive capability of the model was also successfully validated against STH data from 26 control programmes in 16 countries [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in public health morbidity associated with STH is quantified before and after the introduction of mebendazole MDA for eight million Vietnamese children aged 5–14 years for five years, reaching 80% coverage [ 20 ]. To do this we adopted a Markov model published by Montresor et al [ 9 , 19 ]. The model predicts the prevalence of hookworm, A .…”
Section: Methodsmentioning
confidence: 99%
“…A published Markov model developed to monitor MDA programs for school-aged children was adopted to simulate the estimated reduction in STH prevalence due to mebendazole MDA [ 9 , 19 ]. The model we adopted was Transition Probability Matrix Set (TPMS) 4 from the Supplementary Material of Montresor et al (2016), representing the treatment of 1324 school-aged children with mebendazole every 12 months (Table A in S1 Text ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation